Effects of Kalimeris indica on alcohol-induced liver injury through storing Nrf2/HO-1 pathway and gut microbiota - Wang, Mo-Fei; Sun, Tong; Chen, Shi-Yu; Wang, Xue; Li, Hao; Wang, Jia-Qi (Frontiers in Pharmacology, 2024)
Background: Kalimeris indica (L.) Sch. Bip., (K. indica) is a plant classified under the genus Kalimeris within the Asteraceae family. The herb of K. indica has been historically utilized as a traditional medicine. The consumption of excessive amounts of alcohol represents a lifestyle choice that can induce tissue damage and contribute to the development of various health conditions.The HPLC-MS method was used to reveal the chemical composition of K. indica extract. HepG2 cells were used to test the in vitro oxidative stress. C57BL/6 mice were used to construct the in vivo alcohol-induced liver injury. H/E staining and serum ALT and AST levels were tested to assess the in vivo protective effect of ML (50 and 200 mg/kg). GSH, SOD, and CAT levels along with byproduct MDA levels were used to evaluate the in vivo oxidative stress. Immunohistochemical experiments were used to examine the in vivo Nrf2 and HO-1 levels. 16S rRNA gene-based profiling method was used to test the alteration in gut microbiota.Results: 16 compounds were identified from K. indica extract. K. indica treatment reduced oxidative stress in HepG2 cells treated with 5% alcohol. H/E staining results showed that K. indica (50 and 200 mg/kg) alleviated liver injury caused by alcohol administration, eliciting a similar protective effect to the positive drug silymarin. Serum ALT and AST examination gave a consistent result, showing that ML could restore serum ALT and AST levels in mice treated with alcohol. Furthermore, K. indica could also restore GSH, SOD, CAT, and MDA levels in alcohol-treated mice, showing a potent effect on oxidative stress alleviation. Immunohistochemical experiments indicated that K. indica showed the liver protective effect through Nrf2/HO-1 pathway. 16S rRNA gene-based profiling revealed that alcohol treatment caused the alteration in gut microbiota, while K. indica treatment could result in a significantly richer variety of microbial communities compared to the alcohol group.K. indica (ML) has a protective effect on liver injury caused by alcohol administration. The Nrf2/HO-1 pathway and gut microbiota regulation were involved in the ML-induced liver protection. All the results indicate that K. indica has a potential in the treatment of alcohol-induced liver injury.